Community of Inquiry perceptions and divergences between students and instructors. (June 2022) - Englander, Karen; Russell, Bruce
Abstract: While investigations into students' and instructors' experiences of online learning are long-standing, the Covid-19 pandemic caused many universities to suddenly deliver remote programming that had never been done before, or not at this scale. In this study, we investigate a well-established English for Academic Purposes (EAP) Pathway Program that was redesigned for remote teaching and learning. The Community of Inquiry (Garrison, Anderson, & Archer, 1999) was used as both a design tool and research tool. Students completed a questionnaire at two points in the academic year that investigated their experience. Social presence rated lowest and teaching presence rated highest, with an overall score of 4.3 of 5 for their satisfaction with the program. Forty hours of instructor discourse were analyzed concerning their perceptions of how they promoted social, cognitive, and teaching presence in their courses. Results show that students and instructors perceived efficacy of cognitive and teaching presence differently (positive for students, less positive for instructors), but both recognized the shortcomings of social presence in the student experience. This is one of very few studies to investigate online teaching of EAP using the Community of Inquiry framework and demonstrates its efficacy as a lens for understanding curriculum and student experience.